Spillover effects between the carbon and linear shipping markets under COVID-19: A time-varying frequency-domain analysis with applications in portfolio management. (1st October 2022) - Meng, Bin; Chen, Shuiyang; Yang, Mo; Kuang, Haibo
Abstract: With the global consensus on carbon emission reduction, the relationships between the carbon market and conventional financial markets have been extensively studied, while the risk spillover between the carbon and shipping markets is merely addressed. In this paper, we propose a new framework for analyzing the frequency-dependent spillover effects based on the wavelet transformation and DECO-ARMA-GARCH-type modelling, and scrutinize the dynamic interdependence between carbon futures and the stock returns of the top ten linear shipping companies under the impact of the COVID-19 pandemic. We further analyze dynamic portfolio management and hedging efficiency under time-varying market conditions with external shocks. The empirical results indicate that short-term spillovers dominate the spillover effect between the carbon and liner shipping markets and the interdependence is at relatively low levels satisfying the conditions for portfolio hedging. The COVID-19 pandemic has enhanced the correlation between the carbon and liner shipping markets, and hence led to reduced hedging efficiency of carbon futures. Also, due to the impact of the pandemic, the holding of shipping assets should be reduced in return for more carbon assets. This study provides shipping companies with a better understanding of carbon trading for shipping emission reduction and investors with applicable dynamic portfolio management strategies.